Bilateral Smell Preservation is Routinely Possible following Endoscopic Endonasal Approach for Sellar/Suprasellar Lesions - Ting, Kuan-Chung; Wang, Wei-Hsin; Kuan, Edward C.; Lin, Yung-Yang; Lan, Ming-Ying (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective The endoscopic endonasal approach (EEA) has been shown to be an effective means to access sellar lesions. However, there are limited studies centered on evaluating olfactory function after surgery. In this study, we assessed the pre- and postoperative olfactory function of patients who underwent EEA for sellar and suprasellar lesions. The impact of nasoseptal flap use on olfaction was further analyzed.Study Design A retrospective study.Setting A tertiary-care referral center in Taiwan.Participants Patients with sellar and suprasellar lesions who underwent EEA and pre- and postoperative olfaction assessment from August 2015 to March 2018 were included in the study.Main Outcome Measures The patients' olfactory function was examined pre-and postoperatively using the Sniffin' Sticks odor identification test. Data regarding demographics, olfactory scores, pathology, reconstructive technique, graft usage, and extent of resection were retrieved.Results A total of 106 patients (36 males and 70 females) were enrolled, with a mean age of 51 years. There were 76 pituitary tumors, 12 Rathke's cleft cysts, 7 craniopharyngiomas, 7 meningiomas, and 4 other lesions. The nasoseptal flap was used in 39 patients for skull base reconstruction, and these patients had no statistically significant change between pre- and postoperative olfactory scores (p = 0.283). Moreover, a statistically significant improvement of olfactory scores was found in patients in whom the nasoseptal flap was not used.Conclusion Olfactory function may be reliably preserved after EEA, with or without nasoseptal flap harvest and use.
Keywords: olfaction; endoscopic endonasal approach; sellar; hyposmia; nasoseptal flap